A Clickable Oxysterol Photolabel Retains NMDA Receptor Activity and Accumulates in Neurons - Chen, Daniel M.; Ziolkowski, Luke; Benz, Ann; Qian, Mingxing; Zorumski, Charles F.; Covey, Douglas F.; Mennerick, Steven (Frontiers in Neuroscience, 2018)
Oxysterol analogues that modulate NMDA receptor function are candidates for therapeutic development to treat neuropsychiatric disorders. However, the cellular actions of these compounds are still unclear. For instance, how these compounds are compartmentalized or trafficked in neurons is unknown. In this study, we utilized a chemical biology approach combining photolabeling and click chemistry. We introduce a biologically active oxysterol analogue that contains: 1) a diazirine group, allowing for the permanent labeling of cellular targets, and 2) an alkyne group, allowing for subsequent in situ visualization using Cu2+ catalyzed cycloaddition of an azide-conjugated fluorophore. The physiological properties of this analogue at NMDA receptors resemble those of other oxysterols, including occlusion with other oxysterol-like compounds. Fluorescent imaging reveals that the analogue accumulates diffusely in the cytoplasm of neurons through an energy-independent mechanism. Overall, this work introduces a novel chemical biology approach to investigate oxysterol actions and introduces a tool useful for further cell biological and biochemical studies of oxysterols.